Quo Vadis on Film (1912, 1925, 1951, 1985, 2001), The many Faces of Antiquity - Skwara, Ewa (Classica - Revista Brasileira de Estudos Clássicos, 2013)
The Polish novel Quo vadis by Henryk Sienkiewicz was adapted into film five times. Every adaptation was filmed in special circumstances, accompanied by different political situations and each time for a different, specific audience. The comparison and detailed analysis of all versions will bring to light, how and for what purpose has antiquity been translated onto the silver screen. The paper will focus especially on the three adaptations – the American (1951), the Italian (1985) and the Polish one (2001).